Health education of blood donors on HIV viral infections - Elżbieta Bernaciak; Magdalena Lemska; Aleksandra Jaworska-Czerwińska; Beata Pilarska (Kazimierz Wielki University, 2019)
The phenomenon of HIV today is not only a medical problem but also a social one. Due to the pathways of infection, everyone can get infected for us. Currently, there is a steady increase in HIV infection in the world. Convincing people about the lack of danger and the non-characteristic symptoms of infection or their lack, causes that many people do not realize that they are infected. Knowledge about the situations in which we can be infected and the possibility of transmission routes of these viruses can contribute to reducing the number of new infections. The aim of the work was to get to know the state of knowledge about the society about HIV / AIDS and to indicate the role of health education in the fight against infectious diseases. The study included 100 people. The quantitative method was used for research, while the sociological questionnaire was used as a research technique. The analysis of the empirical material shows that the state of knowledge about HIV infection requires education among the population. What's more, the public will be happy to take part in professional training on HIV / AIDS threats. The research shows that trainings should take place periodically, cover various social groups with the cooperation of many non-medical environments. It should be remembered that multisectoral cooperation is a prerequisite for the success of any health improvement program.